Effect of inoculum source and initial concentration on the anaerobic digestion of the liquid fraction from hydrothermal carbonisation of sewage sludge. (November 2018) - De la Rubia, M.A.; Villamil, J.A.; Rodriguez, J.J.; Mohedano, A.F.
Abstract: Hydrothermal carbonisation (HTC) is a relatively new alternative for the management of sewage sludge that allows obtaining a HTC char (hydrochar) with a high heating value (≈22 MJ/kg). The aim of this work has been to study the anaerobic digestion of the liquid fraction generated as by-product during HTC (LFHTC) of dewatered sewage sludge, to get more value to the overall process. For this purpose, three different inocula: granular biomass from industrial reactors treating brewery and sugar beet wastewaters and a flocculent biomass from a full-scale digester of municipal sewage sludge, at two initial inoculum concentrations (IC) (10 and 25 g COD/L) were tested. ANOVA test was applied to evaluate the ultimate methane yield for each IC. The effect was different for each inoculum studied: an increase from 10 to 25 g COD/L increased the methane yield by 23% for brewery waste, achieving the highest value obtained (177 ± 5 mL STP CH4 /g CODadded ), while declining to 99 ± 2 mL STP CH4 /g CODadded for sugar beet; it is not affected by the municipal sludge, yielding around 135 mL STP CH4 /g CODadded . Therefore, among the inocula tested, brewery waste was the most appropriate for the anaerobic digestion of the LFHTC of dewatered sewage sludge at high IC. Graphical abstract: Image 1 Highlights: Anaerobic digestion of the liquid fraction from HTC of sewage sludge was performed. Three inocula at different initial concentration (IC) have been tested. The IC affect in a different way the methane yield depending on the inoculum. The granular sludge gave higher methane yields than the flocculent one.